M.N. Pokrovskii and the Origins of Soviet Historiography - White, James D. (Historical Materialism Book Series, 2024)
Focusing on the career of the Soviet historian M.N. Pokrovskii, the author examines the evolution of historical writing in the first decade of Soviet rule. As Deputy People's Commissar for Education, Pokrovskii was among those who established th